How Halal Awareness and Health Reason can Influence Halal Food Purchasing Decision Among University Students? - Afifah, Triwinda Nur; Riyanti Isaskar; Rini Mutisari; Fitria Dina Riana (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
A List of the 500 Most Powerful Muslims in the World: The Muslim 500 reports that 240 million people, or approximately 86.7% of Indonesia’s population, identify as Muslims according to data collected by The Royal Islamic Strategic Studies Centre (RISSC) in 2024. With this, Indonesia surpasses all other countries in terms of the number of Muslims. At the moment, halal is not just a religious but also a worldwide issue. Contrarily, a large number of MSEs in Indonesia have yet to formally apply for halal certification. This research involved 125 first-year students from Brawijaya University using an accidental sampling-based non-probability sampling technique. Data were collected via a web-based survey and analyzed using scoring analysis, descriptive statistics, and SEM-PLS. Variables in this study include familiarity with halal certification, health concerns, purchase intention, and purchase decision. The results show that intention to purchase halal food items is significantly impacted by health concerns and halal knowledge. In addition, health concerns and purchase intention positively and significantly affect the decision to purchase halal food items.